STUDI TRANSFORMASI ARSITEKTUR CANDI BATU DIENG DITINJAU DARI ANATOMI, TEKTONIKA, PROPORSI, TATA RUANG DAN MASSA SERTA WUJUD REKONSTRUKSI VIRTUALNYA - Steven Nugroho, Michael; P. Herwindo, Rahadhian (Jurnal Riset Arsitektur, 2023)
Abstract - Dieng Temple is one of the oldest stone temple clusters in Central Java and stores about 400 stone temples and now only 9 temples are left standing intact or partially collapsed. Batu Dieng Temple holds a lot of history of architectural development and transformation in the 7th to 8th centuries. The tectonics and architectural anatomy of Batu Dieng Temple can provide evidence of the progress and technology of Nusantara construction in that century, Batu Dieng Temple also stores stories about the relationship between Archipelago Temple Architecture with Temple Architecture in other places such as in North and South India. This study found that there were various kinds of transformations that were studied through the architectural transformation theory written by Mustafa (2010) such as the transformation of creation, cultural borrowing, and variants. In addition, this study also provides an overview of the temples in Dieng that have been found collapsed, such as the head of the Srikandi, Gatotkaca, and Dwarawati temples. Keywords: Batu Temple Architecture, Batu Dieng Temple. Temple Reconstruction, Tectonics, Anatomy